Web system of administration of medical attentions and monitoring for the triage unit: Cayetano Heredia National Hospital case study - Duarte-Jauler, Jennifer (2016)
Despite the lack of an appropriate infrastructure, the number of patients in the Emergency Area of Cayetano Heredia National Hospital has grown in the past few years. The Triage Area is a subarea of the Emergency Area, whose purpose is to classify patients according to their priority level through a quick diagnosis, in order to provide an appropriate level of service to critical patients and optimize the use of hospital resources. This article shows the development of a web system for the integration of the Triage Area with the other subareas of the Emergency area, which would allow the provision of consolidated and shared information in real time, thus speeding up attention process and improving the allocation of the resources critical patients need.